Inter‐radar interference analysis of FMCW radars with different chirp rates. Issue 19 (25th July 2019) - Makino, Yuya; Nozawa, Takuya; Umehira, Masahiro; Wang, Xiaoyan; Takeda, Shigeki; Kuroda, Hiroshi
Abstract : Millimetre‐wave frequency‐modulated continuous wave (FMCW) radar is expected to be widely deployed for advanced driver assistance systems (ADAS) and self‐driving cars. Considering that automotive radars will be deployed in a huge number of cars in future, inter‐radar interference will be a significant problem since inter‐radar interference can cause miss‐detection and/or false detection of the target. As millimetre‐wave automotive radar is not standardised at this moment, it is required to evaluate inter‐radar interference among FMCW radars with various chirp‐rates and chirp durations. This study describes inter‐radar interference analysis in FMCW radars with different chirp rates and simulation results of inter‐radar interference to confirm the validity of the interference analysis.